MR Imaging for Differentiating Contrast Staining from Hemorrhagic Transformation after Endovascular Thrombectomy in Acute Ischemic Stroke: Phantom and Patient Study - You, S.-H.; Kim, B.; Kim, B.K.; Suh, S.-i. (American Journal of Neuroradiology, 2018)
BACKGROUND AND PURPOSE: Early differentiation of contrast staining from hemorrhagic transformation in patients with acute ischemic stroke who have undergone endovascular treatment is critical in preventing the delayed administration of antiplatelet agents. We aimed to demonstrate the usefulness of an immediate postinterventional DWI protocol including B0 and gradient recalled-echo sequences to discriminate those 2 conditions through phantom and preliminary retrospective patient studies.MATERIALS AND METHODS: On 3T MR imaging, the signal intensities of the phantom models consisting of iodinated contrast agents diluted with normal saline and arterial blood were compared using T1WI, T2WI, and gradient recalled-echo sequences. A total 17 patients (8 with hemorrhagic transformation and 9 with contrast staining; 8 men and 9 women; mean age, 72.00 ± 10.91 years; range, 52–90 years) who underwent mechanical thrombectomy for acute ischemic stroke and showed newly appearing hyperdense lesions on immediate (<24 hours) postinterventional nonenhanced CT scans were included in this study. Immediate postinterventional DWI of patients were compared.RESULTS: In the phantom study, iodinated contrast agents diluted with normal saline showed minimal signal drop, while those diluted with arterial blood demonstrated dark signal intensity in the T2WI and gradient recalled-echo sequences. In the patient study, all hemorrhagic transformations and none of the contrast staining demonstrated dark or low signal (<gray matter) intensities similar to those of the vessel in the B0-DWI and gradient recalled-echo images.CONCLUSIONS: According to our preliminary results, contrast staining might be differentiated from hemorrhagic transformation using an immediate postinterventional DWI protocol including gradient recalled-echo sequences. It might be possible to expedite establishment of postinterventional medical treatment strategy.CTFUpostinterventional (24–72 hours) follow-up nonenhanced brain CTCTimmepostinterventional (<24 hours) nonenhanced brain CTGREgradient recalled-echoIODBLiodinated contrast agents diluted with arterial bloodIODNSiodinated contrast agents diluted with normal saline